EDUCATION SYSTEM IN PEOPLE'S REPUBLIC OF CHINA: STRUCTURE AND MAIN DIRECTIONS OF DEVELOPMENT - T. L. Guruleva (Высшее образование в России)
The article explores the structure and the main directions of the development of the education system of the People's Republic of China. The main types of education in China are considered: preschool, initial, average and higher. The author dwells on the structure of professional education and the conditions of its receiving, describes the levels and conditions of the organization of the system of higher and postgraduate education: specialist, bachelor, master, doctor. Features of education of adults in China are revealed. The paper highlights the main directions of education development in China on the 13th five-year period (2016-2020) such as: standardization of schools which carry out compulsory nine-year education, promoting of high school education of the senior step, development of inclusive kindergartens, development of cooperation between the enterprises and educational institutions, creation of world-class higher education institutions and the first-class science, development ofcontinuous education, further training ofteaching staff, education informatization, development of the international educational cooperation.